The learning curve of transanal total mesorectal excision for rectal cancer is associated with local recurrence: results from a multicentre external audit. (9th June 2021) - Van Oostendorp, Stefan E.; Belgers, H. J. (Eric); Hol, Jeroen C.; Doornebosch, Pascal G.; Belt, Eric J. Th.; Oosterling, Steven J.; Kusters, Miranda; Bonjer, H. J. (Jaap); Sietses, Colin; Tuynman, Jurriaan B.
Abstract: Aim: Transanal total mesorectal excision (TaTME) has been suggested as a potential solution for the resection of challenging mid and low rectal cancer. This relatively complex procedure has been implemented in many centres over the last years, despite the absence of long‐term safety data. Recently, concern has arisen because of an increase in local recurrence in the implementation phase. The aim of this study was to assess the correlation between accumulated experience and local recurrences. Method: An independent clinical researcher performed an external audit of consecutive series of all TaTME procedures in six centres in the Netherlands. Kaplan–Meier estimated local recurrence rates were calculated and multivariate Cox proportional hazards regression analysis performed to assess risk factors for local recurrence. Primary outcome was the local recurrence rate in the initial implementation (cases 1–10), continued adoption (cases 11‐40) and prolonged experience (case 41 onward). Results: Six hundred and twenty‐four consecutive patients underwent TaTME for rectal cancer with a median follow‐up of 27 months (range 1–82 months). The estimated 2‐ and 3‐year local recurrence rates were 4.6% and 6.6%, respectively. Cox proportional hazards regression revealed procedural experience to be an independent factor in multivariate analysis next to advanced stage (ycMRF+, pT3‐4, pN+) and pelvic sepsis. Corrected analysis projected the 3‐year local recurrence rates to be 9.7%, 3.3% and 3.5% for the implementation, continued adoption and prolonged experience cohorts, respectively. Conclusion: This multicentre study shows a high local recurrence rate (12.5%) after implementation of TaTME which lowers to an acceptable rate (3.4%) when experience increases. Therefore, intensified proctoring and further precautions must be implemented to reduce the unacceptably high risk of local recurrence at units starting this technique.